William D. Salter papers - Salter, William D., 1795-1869.
Chiefly naval and personal correspondence, together with journal (1831) kept during a voyage from New York, N.Y., to Mobile Bay (Ala.), naval orders, rations, and regulations, and other papers. Includes Salter's correspondence (1828-1864) with his wife, Margaret; correspondence (1850-1853) with secretaries of the navy James C. Dobbin, William A. Graham, and John Pendleton Kennedy, some of which relates to Salter's opposition to abolition of flogging in the navy; and description of Veracruz, Mexico, and the navigation of its harbor.
U.S. naval officer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Forms part of: Naval Historical Foundation collection.
Keywords: Dobbin, James C. -- 1814-1857 -- Correspondence; Graham, William A. -- 1804-1875 -- Correspondence; Kennedy, John Pendleton, -- 1795-1870 -- Correspondence; Salter, Margaret -- Correspondence; United States. -- Navy -- Cruise, 1831.; United States. -- Navy -- Discipline; United States. -- Navy -- Officers; Flagellation; Harbors -- Mexico; Voyages and travels; Mobile Bay (Ala.) -- Description and travel; New York (N.Y.) -- Description and travel; Veracruz (Veracruz-Llave, Mexico) -- Description and travel; Naval officers